Matrix Stiffening Enhances DNCB-Induced IL-6 Secretion in Keratinocytes Through Activation of ERK and PI3K/Akt Pathway - Chung, Hyewon; Oh, Seunghee; Shin, Hyun-Woo; Lee, Yunam; Lee, Hyungsuk; Seok, Seung Hyeok (Frontiers in Immunology, 2021)
Matrix stiffness, a critical physical property of the cellular environment, is implicated in epidermal homeostasis. In particular, matrix stiffening during the pathological progression of skin diseases appears to contribute to cellular responses of keratinocytes. However, it has not yet elucidated the molecular mechanism underlying matrix-stiffness-mediated signaling in coordination with chemical stimuli during inflammation and its effect on proinflammatory cytokine production. In this study, we demonstrated that keratinocytes adapt to matrix stiffening by increasing cell–matrix adhesion via actin cytoskeleton remodeling. Specifically, mechanosensing and signal transduction are coupled with chemical stimuli to regulate cytokine production, and interleukin-6 (IL-6) production is elevated in keratinocytes on stiffer substrates in response to 2,4-dinitrochlorobenzene. We showed that beta 1 integrin activation by matrix stiffening induces focal adhesion kinase-dependent phosphorylation of ERK and the PI3K-Akt pathway, enhancing IL-6 production. Collectively, our results reveal the critical role of matrix stiffening in modulating the proinflammatory response of keratinocytes, with important clinical implications for skin diseases accompanied by pathological matrix stiffening.